ANALISIS MODEL TARIKAN PERGERAKAN PADA SEKOLAH DI KOTA MEULABOH - Chaira Chaira (Universitas Teuku Umar, 2017)
School is one type of land use that can produce trip attraction.This study was conducted to find out the factors that influences the trip attarction of school and build a model that can be used to estimate the tripattraction because of the students vehiclein the school are on Manekroo street, Meulaboh.This study was also conduct to determine the validity of the model by using the value of coefficient determination (R2).Data collection in this study was conducted by calculating the the number of vehicles movementsin the schools reviewed, on coming hours and on out hours.The data are analyzed using multiple linear regression analysis with using SPSS software version 20. The reults indicate that the most influencing variable is the number of students. Calculation results obtained model resylting fromcalculation is Y = 38,575 + 0,911 X1, which Y is the total number of trip attraction in Schools (smp/jam) and X1 is a umber of students. The validity of the model using coefficient determination is 0,993 ; it means the equation is feasible for estimating the value of dependent variable. Keywords : Model, Trip Attraction, School, SPSS